A research study on morbidity including silicotuberculosis among the mine workers of Rajasthan - Prakash Tyagi; Rajesh Mehta (Journal of Integrated Health Sciences)
Background: Stone mines of Western Rajasthan are famous worldwide for its sandstone and white marble. In the drought-stricken state of Rajasthan (in particular in its Western part) mining provides essential support to livelihood generation to more than 2 million people. Mineworkers in these mines work in unsafe conditions, are underpaid, undernourished and suffer with various health problems like silicosis and tuberculosis. This inspired us to estimate the morbidity profile of the mine workers in Jodhpur district of Rajasthan. Material and methods: Using purposive sampling, 221 workers who responded to an appeal for health check up at the various mines and/or at the residential habitats were selected and conducted between August 2009 and April 2010. The collected data was analyzed by using Epi Info3.4.1. Results: Age group of the workers was from 15 to 84 years. 28.6 % of workers were below the age of 30 years. 80 % and 52% of workers were addicted to tobacco and alcohol respectively. 25.33% of workers had past history of tuberculosis treatment. The various complaints of the workers were breathlessness (32.1%), chest pain (24.4%), cough (31.7%) etc. The miners were suffering from chronic respiratory tract infection (21.3%), silico-tuberculosis (11.3%), had digestive tract problem (24.4%), joint problems (23.3%) etc. Conclusions: Looking at poverty, lack of opportunity for other employment for livelihood, lack of health & legal monitoring, absence of treatment for silicosis etc., enormous efforts are required to prevent silicosis in new generation and handle the old cases in a humane manner. But preventable nature of conditions along with huge support of NRHM, voluntary organizations and research together can make a difference in these long lasting problems